Mental health literacy among secondary school students in North and Central Uganda: a qualitative study - Okello, Elialilia S.; Abbo, Catherine; Muhwezi, Wilson W.; Akello, Grace; Ovuga, Emilio (Journal of World Association of Cultural Psychiatry, 2014)
There has been limited effort to explore young people’s perceptions about mental illness in Uganda. For mental health programs targeting young people to succeed, it is important to incorporate their understanding of mental illness, their perceptions about causes of mental illness and their attitudes about mentally ill people. The objective of this study was to explore the mental health of young people in secondary schools in Northern and Central Uganda. Subjects and Methods—This was a qualitative study where 24 focus group discussions (FGDs) were held with young people in secondary schools. Respondents aged 14-24 years were purposively selected from 4 secondary schools in the two regions. During the FGDs, young people’s perceptions and understanding of three areas listed below were explored: meaning of mental health/mental illness; causes of mental illness and attitudes toward mental illness. Data management and analysis was done with the help of Atlas.ti, a-qualitative-analysis software. Thematic analysis approach was employed. Results—FGD participants used concepts like a sound and normal mind, right thinking, normal behavior and normal thoughts to define mental health. Mental illness on the other hand was defined as loss of sense of reality, malfunctioning of the brain, impaired thinking and bizarre behavior. Young people attributed mental illness to; substance abuse (Marijuana, alcohol), witnessing traumatic events (seeing ones your relatives being killed, or being forced to participate in killing-frequently mentioned by young people in Northern Uganda); witch craft, effect of physical illness e.g. HIV/epilepsy, thinking too much, accidents and genetic explanations. They had mixed opinions about interacting with mentally ill individuals. Unpredictability and dangerousness were known to be a recurrent theme among people with negative views about mentally ill. Nonetheless, some FGD participants believed that the level of interaction with mentally ill persons depended on familiarity with mental illness and the severity of the symptoms. Similarly, there were mixed opinions regarding mental illness and work. Three main clusters of responses emerged. These were: i) “mentally ill people should not work”; ii) “mentally ill people should work but..”; iii) “mentally ill people should work like everyone else”. Conclusions—Findings point to key gaps in the knowledge and attitudes of young people that need to be targeted by young-people-focused-interventions for mental health. In order for such interventions to succeed, young people must be able to recognize and respond appropriately to signs of distress, reduced functioning, and other early signs of poor mental health.
Keywords: Young people; Mental health literacy; Schools; Uganda